Beyond the 'refugee crisis': How the UK news media represent asylum seekers across national boundaries. (April 2021) - Cooper, Glenda; Blumell, Lindsey; Bunce, Mel
Migration is one of the most pressing, divisive issues in global politics today, and media play a crucial role in how communities understand and respond. This study examines how UK newspapers ( n  =   974) and popular news websites ( n  =   1044) reported on asylum seekers throughout 2017. It contributes to previous literature in two important ways. First, by examining the 'new normal' of daily news coverage in the wake of the 2015 'refugee crisis' in Europe. Second, by looking at how asylum seekers from different regions are represented. The content analysis finds significant variations in how asylum seekers are reported, including terminology use and topics they are associated with. The article also identifies important commonalities in how all asylum seekers are represented – most notably, the dominance of political elites as sources across all media content. It argues that Entman's 'cascade network model' can help to explain this, with elites in one country able to influence transnational reports.